Pengaruh Media Sosial terhadap Budaya Konsumsi Kuliner di Kalangan PNS Muda di Kota Besar - Asmayadi, Deni (Jurnal Pekommas, 2024)
This research seeks to explore how social media influences and shapes communication behaviors related to culinary consumption among middle-class individuals, particularly young civil servants in major cities. Culinary trends today are predominantly driven by younger generations who are adept with technology. This study examines how young civil servants utilize social media to influence their own culinary habits as well as those of their families. Importantly, previous research has not specifically addressed the social media consumption behaviors of young civil servants or the potential risks they may encounter as public servants. Adopting a qualitative approach, The author conducted in-depth interviews with 10 young civil servants in one civil servant office in Jakarta. The findings indicate that Instagram serves as a primary resource for culinary information, with users frequently engaging with the "save" and "share" features. Some participants reported feeling a sense of addiction to culinary content, which often resulted in impulse purchases and a fear of missing out (FOMO). Additionally, social media-driven culinary choices are made not only to satisfy hunger but also to fulfill other personal motivations